Solar wind‐ and EUV‐dependent models for the shapes of the Martian plasma boundaries based on Mars Express measurements. Issue 7 (15th July 2017) - Ramstad, Robin; Barabash, Stas; Futaana, Yoshifumi; Holmström, Mats
Abstract: The long operational life (2003‐present) of Mars Express (MEX) has allowed the spacecraft to make plasma measurements in the Martian environment over a wide range of upstream conditions. We have analyzed ∼7000 MEX orbits, covering three orders of magnitude in solar wind dynamic pressure, with data from the on board Analyzer of Space Plasmas and Energetic Particles (ASPERA‐3) package, mapping the locations where MEX crosses the main plasma boundaries, induced magnetosphere boundary (IMB), ionosphere boundary (IB), and bow shock (BS). A coincidence scheme was employed, where data from the Ion Mass Analyzer (IMA) and the Electron Spectrometer (ELS) had to agree for a positive boundary identification, which resulted in crossings from 1083 orbit segments that were used to create dynamic two‐parameter (solar wind density, n sw, and velocity v sw ) dependent global dynamic models for the IMB, IB, and BS. The modeled response is found to be individual to each boundary. The IMB scales mainly dependent on solar wind dynamic pressure and EUV intensity. The BS location closely follows the location of the IMB at the subsolar point, though under extremely low n sw and v sw the BS assumes a more oblique shape. The IB closely follows the IMB on the dayside and changes its nightside morphology with different trends for n sw and v sw . We also investigate the influence of extreme ultraviolet (EUV) radiation on the IMB and BS, finding that increased EUV intensity expands both boundaries. Key Points: First empirical solar wind‐ and EUV‐dependent models for the global shapes of the Martian plasma boundaries Largest dynamic range in solar wind pressure studied at Mars (3 orders of magnitude) revealed BS comoving with IMB near subsolar point IMB and BS expand significantly with increased EUV under constrained nominal solar wind conditions